A user-centred collective system design approach for Smart Product-Service Systems: A case study on fitness product design - Fang, Cong; Liu, Wei; Lin, Huan; Qi, Yuge; Tian, Xin; Huang, Yi; Wang, Stephen Jia (The Design journal, 2024)
Emerging technologies have significantly contributed to the evolution of traditional product-service systems (PSS) into smart PSS. This transformation demands a fresh perspective and a more inventive design approach. In response, this study proposes a new User-Centred Collective System Design (CSD) framework and process for Smart PSS design, aiming to enhance stakeholder engagement during the entire design process, thus promoting highly effective and creative design solutions. A case study, titled 'Next-G Smart Fitness PSS Design', was carried out to test and implement this approach, contrasting the results of the CSD method with a designer-centred method. The outcomes showed a marked improvement in product novelty and user desirability of the design outcomes when using the proposed design framework. The proposed CSD framework could offer beneficial insights and user-centric viewpoints for practitioners dealing with complex challenges linked to smart PSS design.